Chronologie des cernes pâles de l’épinette noire ( Picea mariana [Mill.] BSP.) au Québec subarctique : de 706 à 1675 ap. J.-C. - Arseneault, Dominique; Payette, Serge (Géographie physique et Quaternaire, 1998)
The sampling of 1335 tree remains buried in three peatlands from subarctic Québec allowed us to extend by more than 600 years the light ring chronology of black spruce (Picea mariana [Mill.] BSP.) from A.D. 706 to 1339. In total, 257 light rings have been identified over the A.D. 706-1675 period, among which 124 formed before A.D. 1339. Light ringsofA.D.709,713,759,772,774,810, 885, 931, 945, 973, 998, 1056, 1067, 1104, 1126, 1157, 1162, 1170, 1215, 1256, 1258 and 1309 occurred in more than 75 % of all sampled stems. Diagnostic light rings are well distributed in time, except between A.D. 811 and 872 with no light ring occurring in more than 25 % of all sampled tree subfossils. Several unfrequent light-ring years were identified because of the large number of sampled subfossil trees. In addition, light ring frequency was highly correlated between the studied sites, indicating that local site conditions have only minor influence on the formation of light ring compared to climatic conditions. Several diagnostic tree- ring sequences, including an alternation of light rings and narrow rings, are also useful for the crossdating of subfossil spruce. Une récolte de 1335 macrorestes ligneux enfouis dans trois tourbières du Québec subarctique a permis d'allonger de plus de 600 ans la chronologie des cernes pâles de l'épinette noire (Picea mariana [Mill.] BSP.), de l'an 706 ap. J.-C. à l'an 1339 ap. J.-C. Au total, 257 cernes pâles ont été répertoriés entre 706 et 1675 ap. J.-C., dont 124 précèdent l'an 1339. Les cernes pâles formés en 709, 713, 759, 772, 774, 810, 885, 931, 945, 973, 998, 1056, 1067, 1104, 1126, 1157, 1162, 1170, 1215, 1256, 1258 et 1309 ap. J.-C. se trouvent dans plus de 75 % des tiges. De façon générale, ces cernes dia gnostiques sont bien répartis dans le temps, sauf entre 811 et 872 ap. J.-C. où aucun cerne pâle ne s'est formé chez plus de 25 % des épinettes. Grâce au nombre élevé de tiges échantillonnées, plusieurs cernes pâles peu fréquents ont pu être identifiés. De plus, une forte ...